Comparative Effectiveness of Foam Rolling and Percussive Therapy in Post-Exercise Recovery: A Literature Review - Matusiak, Filip; Brzoza, Klaudia (Quality in Sport, 2026)
Background: Foam rolling (FR) and percussive therapy (PT) are common recovery techniques, but direct comparisons of their effects on physiological outcomes are scarce. These techniques—mechanical compression versus high-frequency vibration—trigger different patterns of recovery. Aim: This literature review aims to compare the effects of FR and PT on the recovery of range of motion (ROM), muscle soreness, and physical performance in active populations. Methods: Twenty peer-reviewed studies, including randomised controlled trials (RCTs), reviews, and meta-analyses, were analysed. The outcomes examined included joint range of motion (ROM), pain intensity, blood lactate clearance, and neuromuscular performance. Results: Both modalities significantly increase ROM. PT demonstrated higher levels of acute flexibility improvements in several studies, with up to an 11.4% increase in the range of motion for the hamstring muscle. FR was found to effectively reduce delayed onset muscle soreness (DOMS) at 48 and 72 hours post-exercise. Pearcey et al. (2015) reported that FR maintains neuromuscular efficiency by increasing voluntary activation, thereby accelerating the return to baseline performance. FR also showed advantages in metabolic recovery by improving local blood flow and blood lactate clearance. There was no evidence that either technique used during a warm-up improved acute performance; furthermore, PT occasionally induced transient negative effects due to neural inhibition. The improper use of PT may lead to severe complications, such as rhabdomyolysis. Conclusions: PT is superior for acute flexibility improvements and reductions in muscle stiffness, while FR performs better for metabolic recovery, neuromuscular efficiency, and soreness management. Treatment modalities should be individualised, with an emphasis on functional recovery rather than acute performance.